Demographic, clinical characteristics and cardiovascular disease burden in a Portuguese cohort of older chronic kidney disease patients - Lascasas, Josefina (2021)
Introduction: Chronic kidney disease (CKD) is an independent risk factor for several unfavorable outcomes including cardiovascular disease (CVD), particularly in the elderly, who represent the most rapidly growing segment of the end-stage kidney disease (ESKD) population. Portugal has the highest European unadjusted incidence and prevalence rates of ESKD. In 2012, we started to follow a cohort of elderly CKD patients, we describe their baseline characteristics, risk profile, and cardiovascular disease burden. Methods: All CKD patients aged 65 years and older referred to our department during 2012 were enrolled. Baseline data included: demographic, CKD stage, medication, comorbid conditions. Estimated glomerular filtration rate (eGFR) was calculated by the CKD-EPI formula. Results: A total of 416 patients, 50% referred by primary care physicians, aged 77 ± 7 years, 52% male, with a median eGFR of 32 mL/min/1.73m2 participated in the study. Fifty percent had diabetes (DM), 85% dyslipidemia, 96% hypertension; 26% were current/former smokers, and 24% had a body mass index > 30 kg/m2. The prevalence of CVD was 62% and higher in stage 4-5 patients; in diabetics, it gradually increased with CKD progression (stage 3a < stage 3b < stage 4-5) (39, 58, 82%; p < 0.001). Conclusions: At baseline, our CKD elderly cohort had a higher burden of CVD. The prevalence of CVD was greater than in other European CKD cohorts. Lower level of eGFR was associated with a greater burden of CVD and was more pronounced in diabetics, highlighting the importance of strategically targeting cardiovascular risk reduction in these patients.